2006
DOI: 10.1051/0004-6361:20053782
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-rich disk in the V778 Cygni system resolved

Abstract: Aims. Various scenarios have been proposed to explain the presence of silicate features associated with carbon stars, such as V778 Cyg. We have attempted to constrain these theories by means of mapping water maser emission from V778 Cyg. Methods. The 22 GHz water maser emission from this star has been mapped using MERLIN with an astrometric accuracy of 25 mas.Results. The spatially-and kinematically-resolved maser complex is displaced by ∼190 mas from the position of the C-star as measured 10 years earlier usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 25 publications
5
42
2
Order By: Relevance
“…Water masers observed in some silicate carbon stars, e.g. V778 Cyg Engels & Leinert 1994), are not associated with the winds, but most probably arise in an oxygenrich disk around a companion star in a binary system (Szczerba et al 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Water masers observed in some silicate carbon stars, e.g. V778 Cyg Engels & Leinert 1994), are not associated with the winds, but most probably arise in an oxygenrich disk around a companion star in a binary system (Szczerba et al 2005). …”
Section: Introductionmentioning
confidence: 99%
“…And VLBA H 2 O maser observations toward EU And supported the circum-companion disk (Ohnaka & Boboltz 2008). For V778 Cyg, Szczerba et al (2006) obtained high resolution H 2 O maser maps at 22 GHz and they concluded that the object is composed of a C-rich star and a companion that stores an O-rich disk. Those observations are strong evidences for presence of an O-rich disk around a SCS which is actually a binary system.…”
Section: Discussionmentioning
confidence: 91%
“…While the low number of M-supergiants is likely due to the low number of M-supergiants in general, the OH emitting planetary nebulae and silicate-carbon stars are peculiar within their parent population by having non-standard environments. In planetary nebulae amplification of the radio continuum emission might be held reponsible (Uscanga et al 2012), while the OH masers in silicate-carbon stars may arise like the H 2 O masers in oxygenrich disks associated with binary systems containing a carbon star (Szczerba et al 2006).…”
Section: Discussionmentioning
confidence: 99%